Semiotic Analysis of Hal Kunta Ta'lam Poem by Faruq Juwaidah Based on Michael Riffaterre's Perspective - Maulidiyah, Shinta; Yurisa, Penny Respati (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study aims to analyze the poem "Hal Kunta Ta'lam" by Faruq Juwaidah through Michael Riffaterre's semiotic approach, which includes aspects of heuristic reading, hermeneutic reading, matrix, variant model, and hypogram. This type of research is descriptive qualitative with Riffaterre's semiotic theory approach. The data for this study comes from primary and secondary sources. The primary data sources in this study are stanzas, lines, and words in the poem "Hal Kunta Ta'lam" by Faruq Juwaidah. The secondary data sources in this study are books, proceedings, web articles, and several journals related to semiotics and Michael Riffaterre's poetry. The data analysis technique uses Miles and Huberman's data analysis technique, which consists of data reduction, data presentation, and drawing conclusions. The results of this study are: 1) Heuristic reading is divided into several groups: there are 6 fi'il madhi, 17 fi'il mudhori', 44 isim, and 29 letters. 2) Hermeneutic reading as a rereading generally describes that everything in this world is temporary, and everything will return to its owner. 3) The matrix in this poem is advice about death and reflection on the transience of life. The inner model generally describes the idea of equality in death. Its variant is the comparison between high officials and ordinary people. 4) The hypogram in this poem can be seen from the strong spirit of nationalism shown by the author. Faruq upholds the value of equality while strongly opposing selfishness and efforts to enrich oneself amidst the suffering of others. Abstrak Penelitian ini bertujuan utuk menganalisis puisi Hal Kunta Ta'lam karya Faruq Juwaidah melalui pendekatan Semiotika Michael Riffaterre yang meliputi aspek pembacaan heuristik, pembacaan hermeneutik, matriks, model varian, dan hipogram. Jenis penelitian ini adalah deskriptif kualitatif dengan pendekatan teori semiotika Riffaterre. Data penelitian ini bersumber dari data primer dan data sekunder. Sumber data primer dalam penelitian ini adalah bait, baris, dan kata dalam puisi “Hal kunta Ta’lam” karya Faruq Juwaidah. Sedangkan sumber data sekunder dalam penelitian ini adalah buku, prosiding, artikel web, dan beberapa jurnal yang berkaitan dengan semiotika dan puisi Michael Riffaterre. Teknik analisis data menggunakan teknik analisis data Milles dan Huberman yang terdiri dari reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian ini adalah 1) Pembacaan heuristik terbagi menjadi beberapa kelompok. Terdapat 6 fi’il madhi, 17 fi’il mudhori’, 44 isim, dan 29 hurf. 2) Pembacaan hermeneutik sebagai pembacaan ulang yang secara umum menggambarkan bahwa segala sesuatu di dunia ini hanya sementara, dan segala sesuatu akan kembali kepada pemiliknya. 3) Matriks dalam puisi ini merupakan nasihat tentang kematian dan refleksi tentang kefanaan hidup. Model batin secara umum menggambarkan gagasan tentang kesetaraan dalam kematian. Variannya adalah perbandingan antara pejabat tinggi dan orang biasa. 4) Hipogram dalam puisi ini dapat dilihat dari semangat nasionalisme yang kuat yang ditunjukkan oleh pengarang. Faruq menjunjung tinggi nilai kesetaraan, sekaligus menentang keras keegoisan dan upaya memperkaya diri sendiri di tengah penderitaan orang lain.